Intersubjektif Keadilan Dalam Implementasi Pelayanan Publik Di Kabupaten Banyuwangi - Priyanto, Hary; Noviana, Nana (Majalah Ilmiah DIAN ILMU, 2023)
Bureaucrats in service are obliged to provide fair service to the community. Unfair behavior has an impact on services that are rigid, closed, slow, indifferent, prioritizing what is known, so that there are "underhand" transactions. Unfair implementation of public services causes people to be dissatisfied and reduces the use of service facilities. The difficulty of uncovering the reality of injustice in service is an effect of the silence of society. Injustice continues to take root and grow in public services. The purpose of this study is to describe, analyze, and interpret justice in the implementation of public services in Banyuwangi Regency. This research is based on a qualitative approach according to the constructive and participatory paradigm. Obtain primary data from interviews, secondary data acquisition from literature and regulations that have conformity with the object of research. Data analysis utilized the Atlas Ti application 8.4.23, 2018. The results showed that the implementation of public services in Banyuwangi Regency was related to unfair bureaucrat behavior in serving the community. State oriented based services are considered more important than public oriented bases. Bureaucrats need to internalize the value of justice so that the implementation of quality services upholds human dignity.